Macunaíma, Horace and Virgil - Fonseca, Maria Augusta (Revista do Instituto de Estudos Brasileiros, 1994)
"Carta pras Icaniabas", medial chapter in Mário de Andrade´s Macunaíma o herói sem nenhum caráter, refers to Latin excerpts from authors Virgil and Horace. A discussion about te relationship between tradition and modernity brings forth questions concerning the plurarity of voices whoch pervade the discourse of this Brazilian author.